Beyond the sweetness - Say, Yee How*; Long, Chiau Ming * (Star Media Group Berhad, 2023)
We refer to the thought-provoking article "WHO cancer arm deems aspartame 'possible carcinogen'; consumption limits unchanged"(The Star, July 14; online at bit.ly/aspartamewho), which emphasised our shared concern over the health implications of the use of non-nutritive sweeteners such as aspartame and sucralose in Malaysia.